DETERMINANTS OF IMPOVERISHMENT DUE TO OUT OF POCKET PAYMENTS IN NIGERIA - Aregbeshola, Bolaji Samson; Khan, Samina Mohsin (Journal of Ayub Medical College Abbottabad, 2017)
Background: Poverty is an extreme consequence of out of pocket payments in countries with health systems that do not provide financial risk protection through mandatory health insurance coverage for people in both the formal and informal sectors. The study assessed the determinants of impoverishment due to out of pocket payments in Nigeria. Methods: Secondary data from the Harmonized Nigeria Living Standard Survey (HNLSS) of 2009/10 was utilized to assess factors associated with impoverishment in Nigeria. Household and individual characteristics associated with impoverishment were determined using binary logistic regression. A significance level of p<0.05 was used. Results: Results show that lack of health insurance, having a member above 65 years, large household size, household socio-economic status, type of illness suffered, type of health facility visited, geo-political zones, education of household heads and location were major determinants of impoverishment due to out of pocket health expenditure. Conclusion: Findings from the study show that most households and individuals are vulnerable to financial risk due to this regressive source of payments for health care services. This explains why the level of poverty keeps increasing in spite of the numerous poverty alleviation programs across the country. Policy makers and political actors need to design a new health system financing policy that will increase financial risk protection for people in both the formal and informal sectors. Governments and decision makers have to focus on health as a determinant of economic well-being. Keywords: Out of pocket payments; Impoverishment; Harmonized Nigeria living standard survey; Financial risk protection; Health equity